Comparation of Bevacizumab Intravitreal Injection Effects with and without Yellow Subthreshold Micropulse Laser (577-nm) Combination on Central Macular Thickness and Best Corrected Visual Acuity of Mild-Moderate Diabetic Macular Edema Patients - UTAMI, ALIA NESSA; Djatikusumo, Ari; Khoe, Levina Chandra (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesThe management of macular edema is constantly evaluated, with anti-VEGF therapy being the firstline. Subthreshold micropulse laser (SML) has been proposed as alternative adjuvant. Previousretrospective studies demonstrated the effectiveness of 577-nm SML as monotherapy in macularedema with CMT below 400 ?m. However, prospective data on the effectiveness of SML as adjuvantis lacking. The aim is to assess the effect of the combination of bevacizumab and 577-nm SML lasercompared to bevacizumab monotherapy on central macular thickness and visual acuity in mildmoderatediabetic macular edema patients. MethodsA prospective randomized clinical trial was performed on diabetic macular edema patients withmacular thickness range of 300-600 ?m. Subjects are divided into two groups. The control groupreceived a standard protocol and the study group received a yellow SML laser adjuvant one weekafter injection. Patients underwent follow-up assessment of visual acuity and central macularthickness at 28 and 35 days post-injection. Results26 subjects were equally divided into study and control groups. Significant decrease in CMT werefound in study group (p=0.011 and 0.014) and the control group (p=0.006 and p=0.001). However,there was no significant difference in ?CMT values between the two groups in the 28-day (p=0.317)and 35-day controls (p=0.84). There was no difference in ?BCVA ETDRS between the study andcontrol groups at 28 days (p=0.568) and 35 days (p=0.128) after injection. ConclusionThe combination of SML and intravitreal bevacizumab can reduce central macular thickness andimprove visual acuity but there was no significant difference with standard monotherapy.